RELATIONSHIP BETWEEN ENVIRONMENTAL SANITATION AND THE INCIDENCE OF DIARRHEA IN TODDLERS IN THE WORK AREA OF THE CIRENDEU HEALTH CENTER, SOUTH TANGERANG CITY IN 2022 - Nurul Anggraini; Dewi Purnamawati (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
According to the World Health Organization (WHO) each year diarrhea causes 525,000 deaths in toddlers and results in 1.7 million children in the world suffering from diarrheal diseases. Riskesdas results in 2018 showed the prevalence of diarrhea in all ages as much as 8%, in toddlers as much as 12.3%, and in infants as much as 10.6%. Sample Registration System The coverage of diarrhea services in 2021 at all ages was 33.6% while in toddlers it was 23.8%. This research is a type of quantitative research with a cross-sectional study design that uses purposive sampling techniques. This research was conducted on mothers who have toddlers in the Cirendeu Health Center Working Area in 2022. The sample in this study was 77 respondents. The data analysis technique in this study was univariate and bivariate using the Chi-square test. Bivariate test results using the Chi-Square test with α = 0.005  found results There is a relationship between environmental sanitation and the incidence of diarrhea in toddlers in the Cireundeu Health Center Working Area in 2022 with (p-value =  0.003 ≤ α = 0.05) and a Odds ratio value of 6.042. Based on the results of the study, this study states that there is a relationship between environmental sanitation and the incidence of diarrhea in toddlers in the Cireundeu Health Center Working Area in 2022. Provide education on the importance of trash cans that are closed and tightly closed.